The Effect of Covid-19 on Human Immune System: A Literature Review - Zefanya, Amarthya Belleza Puspa; Yuliwulandari, Rika (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
ABSTRACT The coronavirus disease (COVID-19) was first reported at the end of 2019 in Wuhan, China. The COVID-19 outbreak has spread to several countries quickly and transmitted from animals like bats. The COVID-19 pandemic caused by the SARS-CoV-2 virus has had a significant impact on public health globally. One of the main aspects that is affected is the human body’s endurance or immune system. This research aims to examine how COVID-19 infection affects the immune response and the underlying menchanisme. This virus is known to trigger an excessive innate and adaptive immune response, which can lead to dangerous conditions such as a cytokine storm. In addition, patients with comorbid conditions such as diabetes, obesity, and heart disease tend to experience a decline in immune function, making them more vulnerale to severe COVID-19 symptoms. On the other hand, COVID-19 infection also impacts the long-term immune system, where some patients exhibit “long COVID” symptomps, indicating prolonged immune dysfunction. This study also reviews the important roles of nutrition, physical acitivity, and stress management in supporting the immune system during the pandemic. The finding suggest the importane of integrated prevention strategies to enhance immune health, particulary among vulnerable Keywords: COVID-19, pandemic, immune system, immune respon